Incidence and mutation rates of Huntington's disease in Spain: experience of 9 years of direct genetic testing. Issue 3 (16th February 2005) - Ramos-Arroyo, M A; Moreno, S; Valiente, A
Abstract : Background: Prior to the discovery of the Huntington's disease (HD) mutation, the prevalence, incidence, and new mutation rates for this disease were based on the presence of progressive choreic movements and a positive family history. Objective: To evaluate the uptake of the HD genetic analysis in Spain, and to provide additional information on the epidemiology of this disease from the experience of 9 years of direct genetic testing. Methods: From 1994 to 2002, CAG repeat length was determined in 317 patients with symptoms compatible with HD. In all cases, demographic, clinical, and family data were carefully reviewed. Results: HD diagnosis (CAG repeat length ⩾36) was confirmed in 166 (52%) symptomatic cases. Of these, 76 (45.8%) reported a positive family history and in 21 cases (12.7%) family history was negative. New mutation events were genetically proven in three families and highly suspected in another, estimating that the minimum new mutation rate for HD in our population is >4%, with a potential mutation rate of 8%. More than 16% of all HD cases had late onset (>59 years) of symptoms, and in three quarters of these the family history was negative. The incidence rate for the autonomous communities of Navarra and the Basque country, based on the number of newly diagnosed cases by genetic testing, was 4.7 per million per year. Conclusions: Direct HD genetic testing shows that the incidence and mutation rates of the disease are 2–3 times higher than previously reported. We also demonstrated the relevance of CAG repeat length assessment in diagnosing patients with late onset of symptoms and negative family history for HD.